CBCT Analysis of Maxillary and Sphenoidal Sinuses for Forensic Age and Gender Estimation: A Retrospective Study - Amruta J Potekar; Rashmi Venkatesh; Chandramani B More; Deepa J Patil (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Age and gender estimation are fundamental in forensic identification, especially in crime investigation, cases of mass disasters and unidentified body remains. Paranasal sinuses, especially maxillary and sphenoidal, are unique, durable, and sexually dimorphic and well-protected within skull, resistant to trauma and decomposition. Cone Beam Computed Tomography (CBCT) enables precise Three-dimensional (3D) morphometric analysis of these anatomical structures, making them valuable markers for forensic age and gender determination. Aim: To evaluate the morphological (volumetric) characteristics of the maxillary and sphenoidal sinuses using CBCT to assess their potential in forensic age and gender estimation. Materials and Methods: The present Institutional-based retrospective study was conducted between September 2025 to November 2025 on CBCT archives from Department of Oral Medicine and Radiology, K M Shah Dental College and Hospital, Sumandeep Vidyapeeth (Deemed to be University), Vadodara, Gujarat, India. CBCT Digital Imaging and Communications in Medicine (DICOM) files of maxilla/both arches covering maxillary and sphenoidal sinus was selected for analysis. Total CBCT scans of 142 individuals aged 21-75 years were analysed and volumetric measurements of bilateral maxillary and sphenoidal sinus were recorded by semi-automatic segmentation method using 3D Slicer software and statistically analysed to determine correlations with age and gender. Inclusion and exclusion criteria were strictly applied to ensure sample consistency. For statistical analysis Chi-square test, Mann-Whitney, KruskalWallis tests and Logistic regression analysis were done, p-values less than 0.05 were regarded as statistically significant. Results: Significant variations in sinus dimensions were observed between different genders and age groups. The median volumes of the maxillary sinus (males: 13,574.75 mm³; females: 11,210.30 mm³) and the sphenoidal sinus (males: 4,918.71 mm³; females: 4,017.23 mm³) were significantly greater in males than in females, with p-values of 0.023 and 0.02, respectively. Correlation analysis revealed a statistically significant (p-value